Measurement of electrons from beauty-hadron decays in pp and Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; et al. (Physical review, 2023)
The production of electrons from beauty-hadron decays was measured at midrapidity in proton-proton (pp) and central Pb-Pb collisions at center-of-mass energy per nucleon-nucleon pair √sNN = 5.02 TeV, using the ALICE detector at the LHC. The cross section measured in pp collisions in the transverse momentum interval 2<pT<8GeV/c was compared with models based on perturbative quantum chromodynamics calculations. The yield in the 10% most central Pb-Pb collisions, measured in the interval 2<pT<26GeV/c, was used to compute the nuclear modification factor RAA, extrapolating the pp reference cross section to pT larger than 8 GeV/c. The measured RAA shows significant suppression of the yield of electrons from beauty-hadron decays at high pT and does not show a significant dependence above 8GeV/c within uncertainties. The results are described by several theoretical models based on different implementations of the interaction of heavy quarks with a quark-gluon plasma, which predict a smaller energy loss for beauty quarks compared to light and charm quarks.